FITNESS FOR SERVICE OF SEPARATOR WITH CRACK LIKE FLAWS BASED ON API 579 - SEPTIANA (NIM : 13106077); Dosen Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, YANA
In oil and gas industry, equipments in the production process consist of static equipment and dynamic equipment. With greater time of use, and increase of operational load and temperature, those equipments would reduce in terms of reliability and suffer functional failure, due to corrosion, geometrical defects, tears or cracks. To see the effects of reliability degradation, a Fitness For Service analysis is required. In this final project, the equipments are analyzed using the standards of API 579 part 9 level 1 and 2. This method consist of several complicated steps. A software, using Mathcad 14, is created to assist in calculations for each level. The case studied in this research is a separator in Suban Gas Statiun with the number of component 215-V-201 that has suffered from cracks. The inspection results show that there are 4 crack failures in internal nozzle 5A, categorized as surface flaw, located in the inner surface perpendicular to the weld joint. The length of the crack (2c) is 3.464 in, 3.364 in, 3.15 in, 3.071 in. The depth of the crack (a) is 0.118 in. The calculations based on API 579 show that the crack failure in the separator falls under the acceptance criteria of level 1 and level 2, which means that the separator can continue to operate. Then analyze continued to indentify the parameters that influence integrity of component that has suffered from cracks. That parameters is the depth and length of crack, and operation pressure. It can be concluded that if parameters value become higher, then integrity of component will be decliner, so component not safe to operate.